Effect of angle of turn on loss characteristics and flow rectification of curve diffuser - Hau, Chin Yong; Nordin, Normayati; Rasidi, Shamsuri Mohamed; Teo, Wen Yong; Anuar, Muhammad Musleh; Shariff, Muhammad Zahid Firdaus (Semarak Ilmu Publishing, 2022)
Curve diffuser is often used in HVAC and wind tunnel systems to provide pressure recovery and avoid excessive energy loss to the surrounding environment. Performance of curve diffuser is disturbed mainly by the presences of flow separation and secondary flow vortices occurred due to the effect of turning angle, in which scarce literature found. In this study, the effect of turning angle from 30° to 180° configured with an area ratio of 1.60 to 4.00 and inflow Reynolds number of 5.934x104 – 1.783x105 on loss characteristics and flow rectification of curve diffuser is investigated with optimum configuration is proposed. Performance of curve diffuser is evaluated in terms of pressure recovery and flow uniformity using ANSYS CFD equipped with validated Standard k-ɛ model (ske) and enhanced wall treatment of y+ = 1.2 - 1.7. Results show that performance of pressure recovery and flow uniformity decreases respectively by 85.71% and 45.84% as the angle of turn increases from 30° to 180°. Curve diffuser with minimum angle of turn 30o , optimum area ratio 2.16 and intermediate Rein 8.163x104 turns out to be the best configuration to provide pressure recovery of 0.399 and flow uniformity of 3.630 m/s.